2017
DOI: 10.1186/s13075-017-1444-4
|View full text |Cite
|
Sign up to set email alerts
|

Urine S100 proteins as potential biomarkers of lupus nephritis activity

Abstract: BackgroundImproved, noninvasive biomarkers are needed to accurately detect lupus nephritis (LN) activity. The purpose of this study was to evaluate five S100 proteins (S100A4, S100A6, S100A8/9, and S100A12) in both serum and urine as potential biomarkers of global and renal system-specific disease activity in childhood-onset systemic lupus erythematosus (cSLE).MethodsIn this multicenter study, S100 proteins were measured in the serum and urine of four cSLE cohorts and healthy control subjects using commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 37 publications
(42 reference statements)
3
38
0
Order By: Relevance
“…A limit of detection of 3 nM (~36 ng/ml) was demonstrated. This value lies within the clinically relevant range demonstrated by Turnier et al for patients with lupus nephritis and can be used as a reference value for patients with bladder cancer [8,41,42]. These results show the potential of using this novel material platform to detect biomarkers in point-of-care applications using patients' urine without any sample pre-treatment and/or complicated amplification steps.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…A limit of detection of 3 nM (~36 ng/ml) was demonstrated. This value lies within the clinically relevant range demonstrated by Turnier et al for patients with lupus nephritis and can be used as a reference value for patients with bladder cancer [8,41,42]. These results show the potential of using this novel material platform to detect biomarkers in point-of-care applications using patients' urine without any sample pre-treatment and/or complicated amplification steps.…”
Section: Introductionsupporting
confidence: 71%
“…Therefore, the overexpression of S100A4 protein may be of value as a biomarker of bladder cancer progression. Urine levels of S100A4 for bladder cancer are not reported in the literature but Turnier et al showed median urine levels of S100A4 around 0.1 nM for healthy controls and median urine levels ranging from 0.5 to 1 nM for patients with lupus nephritis using a commercially available ELISA kit [8].…”
Section: Introductionmentioning
confidence: 99%
“…Detection of a concentration as low as 300 pM of the S100A4 protein in synthetic urine is experimentally demonstrated. This falls within the concentration range being reported as clinically relevant [24], therefore showing the potential of this active platform for label-free biosensing.…”
supporting
confidence: 79%
“…2d). A lowest concentration of 3 nM was detected, which is within the clinically relevant range [8].…”
Section: Passive Microring Resonator Sensingmentioning
confidence: 76%